Antinuclear Antibodies With a Homogeneous and Speckled Immunofluorescence Pattern Are Associated With Lack of Cancer While Those With a Nucleolar Pattern With the Presence of Cancer - Gauderon, Amandine; Roux-Lombard, Pascale; Spoerl, David (Frontiers in Medicine, 2020)
Background Different antinuclear auto-antibodies (ANA) patterns have been associated with the presence of cancer, while other are typically seen in autoimmune diseases. This study aims to investigate the association between ANA and cancer, focusing on patients with ANA with a nucleolar indirect immunofluorescence (IIF) pattern. Materials and Methods ANA patterns and positivity of antibodies against nuclear antigens (NA), in particular those responsible for a nucleolar ANA pattern and/or associated with systemic sclerosis (CENP-A/B, fibrillarin, Ku, NOR-90, PM/Scl-100, PM/Scl-75, RNAP-III, Scl-70, Ro52/TRIM21 and Th/To) were analyzed and correlated to an internal database of patients with cancer. Results The study included 15’728 patients who had an ANA analysis, 386 patients who had immunodot analysis for antibody/ies against/to specific NA and 15’701 patients diagnosed with cancer. The presence of ANA with a nucleolar pattern showed an increased relative risk (RR 1.5, 95%CI 1.03-2.3) for an associated cancer. Anti-Scl70 and anti-RNAP-III were associated with cancer in 15% and 14% respectively. The presence of ANA with a homogeneous & speckled (HS) pattern was significantly associated with the absence of cancer (p < 0.01). Patients with a HS pattern were found to have a lower relative risk (RR 0.7, 95%CI 0.5-0.9) of having cancer compared to those with other patterns. Conclusions Larger studies are needed to investigate which particular antibody/ies against/to specific NA is responsible for the association between nucleolar ANA and cancer, but anti-Scl70 and anti-RNAP-III, which is frequently associated with the presence of anti-RNAP-I, are good candidates to explain this association.